Vì ΔABC = ΔA′B′C′ ⇒ ∠B'C'A' = ∠BCA ⇒ ΔDBC cân tại D ⇒ DB = DC
Ta có: ∠B'C'A' + ∠B'C'A = 90°, ∠BAC + ∠BCA = 90°, ∠B'C'A' = ∠BCA
⇒ ∠B'C'A = ∠BAC ⇒ ΔDAB cân tại D
Kẻ DH ⊥ BC.
Theo định lý Ta-lét, ta có:
\(\dfrac{DH}{AB}\) = \(\dfrac{DC}{AC}\) = \(\dfrac{1}{2}\)
Lại có:
\(S_{CBD}\: =\: \dfrac{1}{2}BC.DH\)
\(S_{ABC}\:=\:\dfrac{1}{2}BC.AB\)
⇒ \(\dfrac{S_{CBD}}{\text{S}_{ABC}}\: =\: \dfrac{DH}{AB}\: =\dfrac{1}{2}\: \). (1)
Vì ΔABC = ΔA′B′C′ ⇒ \(\dfrac{S_{CBD}}{\text{S}_{A\text{'}B\text{'}C}}\text{ }\text{=}\text{ }\dfrac{1}{2}\text{ }\)(2)
Từ (1) và (2) ⇒ \(S_{CBD}\:=\:S_{BAD}\:=\:S_{B'DCA'}\text{ } \)
⇒ \(\dfrac{S_{CBD}}{S_{BADB'A'}}\:=\:\dfrac{1}{3}\)